The study of chaotic dynamics of an eco-epidemiological predator-prey model with alternative food - Roy, Prodip; Sarkar, Abhishek; Agnihotri, Kulbhushan; Das, Krishna Pada (Journal of AppliedMath, 2023)
Parasites can alter the quality and quantity of participants. On the other hand, the spread of diseases between individuals or species is an important research topic. Here we consider a tritrophic food model in which bacteria spread among the animal's environment where other nutrients are present. We analyze the local stability of the model around the efficiency of the equation. We also report significant numbers of offspring in terms of ecology and disease and use these numbers to analyze community structure of the sample. We started from this situation as a model. Our numerical results show that at low infection level the body causes conflict, but at high infection level conflict prioritizes safety. Our findings therefore challenge previous models’ predictions that the parasite has a negative impact. We also looked at the impact of other foods on chaotic dynamics. When other nutrients increase, stress does not change, but when other nutrients decrease, chaos disappears and the disease among animals is eliminated from the body.